Taxonomic status of Velinoides Matsumura (Hemiptera: Reduviidae: Harpactorinae) inferred from mitochondrial and nuclear genes - Liu, Hui; Zhao, Ping; Li, Shujuan; Cai, Wanzhi (Zootaxa, 2009)
In this study, we used three mitochondrial genes (cyt b, COI, and 16S rRNA) and one nuclear gene (28S rRNA) to evaluate the current taxonomic status of the genus Velinoides erected by Matsumura. Phylogenetic analyses of genes using maximum parsimony, maximum likelihood, and minimum evolution resulted in different phylogenetic trees. However, the combined dataset analysis revealed better phylogenetic relationships. The constructed phylogenies appeared to be largely congruent with morphological studies. Results based on the molecular data strongly supported that the C. dilatatus, the type species of Velinoides, was the sister group to all other species of the genus Coranus Curtis. Incorporation with the morphological and cytogenetic characteristics, we proposed that Velinoides is of subgeneric status, the genus Coranus Curtis should be divided into two subgenera, Velinoides Matsumura and Coranus Curtis. Our phylogenetic results suggested that the 28S rDNA gene segment alone might not be an optimal molecular marker for the phylogeny of the genus Coranus Curtis.